Repere ale artei teatrale în cultura populară română - Orian, Georgeta (Studia Romanica Posnaniensia, 2014)
The paper aims to offer a synthetic perspective upon the dramatic genre in the Romanian folklore. We present several preliminary elements within a short historical account of the dramatic manifestations; afterwards we create an inventory of the forms of theatrical arts, following the first historical records, a description of the rituals and props in order to depict the folk syncretism and all its beauty. The working instruments are those offered by historiography and the methodology in the field as well as the ethnographic description. Although less consistent than the folk poetry or epic, folk theatre contributes to the complexity and flavour of Romanian folklore. The unseen mechanisms of syncretism have functioned and are still functioning, generating new forms of folk art. The laic and the religious, the traditional and the modern, the epic and the drama, the masks, the dances as well as the costumes and the props – all these contribute to the survival of this particular folk genre. Moreover, being the least discreet of all Romanian folk genres, the folk theatre represents also an element of attraction and cultural export nowadays.